2017
DOI: 10.1038/s41598-017-03589-w
|View full text |Cite|
|
Sign up to set email alerts
|

New noninvasive index for predicting liver fibrosis in Asian patients with chronic viral hepatitis

Abstract: We developed an optimal noninvasive index comprising routine laboratory parameters for predicting cirrhosis in chronic hepatitis B (CHB) and chronic hepatitis C (CHC) patients. This study included 992 CHB patients and 1,284 CHC patients who received liver biopsy. We developed the new index, named modified Fibrosis-4 (mFIB-4) according to four independent variables of the model: age, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and platelet count. The formula of the mFIB-4 index is 10 × Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
6
34
1
1
Order By: Relevance
“…We previously reported that an mFIB-4 cutoff value of 1.8 exhibited an AUROC of 0.739 (sensitivity 67.8% and specificity 72.6%) for predicting significant fibrosis (F2-F4). 23 We hypothesize that noncirrhotic patients with mFIB-4 < 1.5 in our current cohort might have had a fibrosis stage of F0 or F1 at the baseline and thus minimal risk of HCC during NA therapy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We previously reported that an mFIB-4 cutoff value of 1.8 exhibited an AUROC of 0.739 (sensitivity 67.8% and specificity 72.6%) for predicting significant fibrosis (F2-F4). 23 We hypothesize that noncirrhotic patients with mFIB-4 < 1.5 in our current cohort might have had a fibrosis stage of F0 or F1 at the baseline and thus minimal risk of HCC during NA therapy.…”
Section: Discussionmentioning
confidence: 89%
“…Taken together, these studies support the role of FIB‐4 measurement in stratifying the risk of HCC in CHB patients receiving NA therapy. We recently proposed a new noninvasive fibrosis index, mFIB‐4, and demonstrated its superior diagnostic accuracy for predicting liver fibrosis in patients with CHB compared with other common indices, including FIB‐4 and APRI . We posit that mFIB‐4 exhibits higher predictive accuracy in stratifying the risk of HCC in CHB patients receiving NA therapy compared with FIB‐4 and APRI.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, PLTs may release growth factors that stimulates cellular growth, proliferation, healing, and cellular differentiation, such as transforming growth factor-β and fibroblast growth factor, which increases invasive capacity and proliferation of cancer cells (5,14,15). In addition, PLTs and numerous noninvasive models, such as AAR, AST to PLT ratio index (APRI) (16), fibrosis-4 (FIB-4) (17), Pohl score (18), FibroQ (19) and Lok index (20), have been reported to predict liver fibrosis and are therefore considered diagnostic indicators of cirrhosis (20)(21)(22)(23). Previous studies demonstrated that PLTs represent independent factors of cancer recurrence and prognosis (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment for liver fibrosis has advanced considerably, but no effective anti-fibrotic drugs are available. 2 – 4 In recent years, traditional Chinese medicine formulations have been shown to exhibit great efficacy in treating liver fibrosis, with good prospects for application. 5 10 Traditional Chinese medicine practitioners believe that “phlegm to hinder collaterals” is the basic pathogenesis of liver fibrosis, and therefore, suggest “eliminating phlegm and freeing channels” as one of the potential treatments for liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%